PENGARUH SUPERVISI KEPALA SEKOLAH DAN PENGUASAAN TEKNOLOGI GURU TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR NEGERI DI KECAMATAN GUNUNG AGUNG - Veronica Lisa Febriani; Siti Nurlaila; Muhfahroyin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' learning outcomes are one of the indicators of successful learning processes. A preliminary survey at Public Elementary Schools in Gunung Agung District revealed that 53.52% of students had not achieved the KKTP. This study aimed to determine the effect of principal supervision (X1) and teachers' technological mastery (X2) on students' learning outcomes (Y) using a quantitative ex post facto design with 48 teachers from five schools. Data were collected through questionnaires and documentation, analyzed using multiple linear regression with SPSS. Findings showed principal supervision had a significant effect (t = 3.332; Sig. = 0.002 < 0.05). Teachers' technological mastery also had a significant effect (t = 6.463; Sig. = 0.000 < 0.05). Simultaneously, both variables had a significant effect (F = 162.504 > F-table = 3.20; Sig. = 0.000). R-squared = 0.878 indicated that 87.8% of the variance was explained by the two variables.